Chapter 5 'Rapt Up with Joy': Children's Emotional Responses to Death in Early Modern England - Newton, Hannah (Palgrave Studies in the History of Childhood, 2016)
This chapter takes advantage of recent insights from the history of emotions to offer a fresh perspective on children's emotional responses to death. Drawing on a range of printed and archival sources, it argues that children expressed diverse and conflicting emotions, from fear and anxiety, to excitement and ecstasy. In contrast to Houlbrooke and Stannard, I have found that children's responses seem to have changed little over the early modern period. This continuity is largely due to the endurance of the Christian doctrine of salvation, with its hauntingly divergent fates of heaven and hell.